2015
DOI: 10.1177/0038038515582160
|View full text |Cite
|
Sign up to set email alerts
|

‘It’s Nothing Personal’: Anti-Homosexuality in the British Workplace

Abstract: Scholarship on homophobia has been critiqued for being individualistic and psychological, failing to account for structural inequalities, experiences of homophobia and discursive manifestations of homophobia. This Economic and Social Research Council funded study attempts to address some of these concerns by focusing on the experiences of lesbians, gay men and bisexuals (LGBs) in relation to bullying, harassment and discrimination in the British workplace. We examine what homophobia is understood to be and how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 74 publications
0
22
0
1
Order By: Relevance
“…Nas empresas, os comportamentos preconceituosos e discriminatórios podem infl igir danos pessoais e profi ssionais, tais como: a possível perda de emprego em virtude da orientação sexual; a menor probabilidade de obtenção de promoções e ascensão na carreira profi ssional (Einarsdóttir et al, 2015). Ademais, as avaliações do desempenho são fortemente infl uenciadas quando o alvo da avaliação é um homossexual (Siqueira & Zauli-Fellows, 2006).…”
Section: O Preconceito Contra Homossexuais No Ambiente De Trabalhounclassified
“…Nas empresas, os comportamentos preconceituosos e discriminatórios podem infl igir danos pessoais e profi ssionais, tais como: a possível perda de emprego em virtude da orientação sexual; a menor probabilidade de obtenção de promoções e ascensão na carreira profi ssional (Einarsdóttir et al, 2015). Ademais, as avaliações do desempenho são fortemente infl uenciadas quando o alvo da avaliação é um homossexual (Siqueira & Zauli-Fellows, 2006).…”
Section: O Preconceito Contra Homossexuais No Ambiente De Trabalhounclassified
“…Incivility is defined as low‐intensity deviant, ambiguous antisocial behaviour that is purposefully intended to harm or insult someone else (Andersson & Pearson, ). Sexual minority employees may excuse or experience uncertainty related to their colleagues' comments (Einarsdóttir, Hoel, & Lewis, ). Further, colleagues will typically report their behaviour as nondiscriminatory and “not personal” (Einarsdóttir et al, ).…”
Section: Job Demands–resources Modelmentioning
confidence: 99%
“…Sexual minority employees may excuse or experience uncertainty related to their colleagues' comments (Einarsdóttir, Hoel, & Lewis, ). Further, colleagues will typically report their behaviour as nondiscriminatory and “not personal” (Einarsdóttir et al, ). Zurbrügg and Miner () reported that when examining the relation between gender, sexual orientation, and workplace incivility, sexual minority women endorsed the highest level of workplace incivility in their sample.…”
Section: Job Demands–resources Modelmentioning
confidence: 99%
“…anti-homophobic bullying policies. It is interesting to look at the school as a workplace, and to consider it in the context of a study by Einarsdottir, Hoel and Lewis (2015) examining anti-homosexuality in the British workplace (the authors use this term instead of 'homophobia', in order to capture the broader structural nature of the issue that goes further than derogatory remarks). They found that, in studying six organisations, anti-homosexuality was indirect and hard to pinpoint, with LGB interviewees reluctant to label colleagues as homophobic.…”
Section: Homophobia and Sexism In Schoolmentioning
confidence: 99%